The Economics of Providence / L'économie de la providence : Management, Finances and Patrimony of Religious Orders and Congregations in Europe, 1773 - ca. 1930 / Gestion, finances et patrimoine des ordres et congregations en Europe, 1773 - ca. 1930 - Koppen, Jimmy, 1977-; Tyssens, Jeffrey; De Maeyer, Jan, 1952-; Dijck, Maarten van (Book collections on Project MUSE., 2012)
During the French Revolution almost all monasteries and abbeys were suppressed and their possessions seized. Yet after the French Revolution many religious institutes were very successful in re-establishing themselves, sometimes accumulating large patrimonies, against the background of often hostile political forces. This book deals with the question of how the religious orders and congregations rebuilt their patrimony, a necessary prerequisite for the growth of the number of religious, educational and charitable services. The authors discuss the (real or supposed) wealth, the financial structures, and the management and juridical foundations of the orders and congregations in Italy, Spain, Portugal, France, Luxembourg, Belgium, Ireland, and the United Kingdom from the late eighteenth century to the 1930s.